RNA modification - Chanfreau, Guillaume F. (Cambridge, MA : Academic Press, an imprint of Elsevier, 2017)
RNA Modification, volume 41, examines the powerful ability to regulate the function of RNA molecules or modify the message transmitted by RNA molecules. This field has recently seen a very rapid progress in our understanding of the mechanism and enzymes involved in RNA modification. This volume presents some of the most recent advances in the identification and function of enzymes involved in modifying RNA molecules.Features authoritative expertise from recognized contributors to the field. Presents the most recent advances in the rapidly evolving field of RNA modification.--
Includes bibliographical references.
Keywords: Nucleosidases. -- Enzymes; RNA editing. -- Nucleic acids